2015
DOI: 10.1111/cas.12649
|View full text |Cite
|
Sign up to set email alerts
|

Expression and regulatory effects on cancer cell behavior of NELL1 and NELL2 in human renal cell carcinoma

Abstract: Neural epidermal growth factor-like like (NELL) 1 and 2 constitute a family of multimeric and multimodular extracellular glycoproteins. Although the osteogenic effects of NELL1 and functions of NELL2 in neural development have been reported, their expression and functions in cancer are largely unknown. In this study, we examined expression of NELL1 and NELL2 in renal cell carcinoma (RCC) using clinical specimens and cell lines. We show that, whereas NELL1 and NELL2 proteins are strongly expressed in renal tubu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 39 publications
4
46
0
Order By: Relevance
“…For example, NELL-1 has been found to be epigenetically silenced via methylation in several carcinomas, including colon adenocarcinoma, 26 esophageal adenocarcinoma, 27 as well as renal cell carcinoma. 28 Our study, in combination with our previous observations, 25 suggests that the opposite is true in skeletal sarcomas, including consistent NELL-1 overexpression in both osteosarcoma and chondrosarcoma. The bioactive effects of NELL-1 in skeletal sarcomas remain a matter of speculation; however, recent understanding of NELL-1 as an integrin b1 ligand may reveal new insights.…”
Section: Discussionsupporting
confidence: 81%
“…For example, NELL-1 has been found to be epigenetically silenced via methylation in several carcinomas, including colon adenocarcinoma, 26 esophageal adenocarcinoma, 27 as well as renal cell carcinoma. 28 Our study, in combination with our previous observations, 25 suggests that the opposite is true in skeletal sarcomas, including consistent NELL-1 overexpression in both osteosarcoma and chondrosarcoma. The bioactive effects of NELL-1 in skeletal sarcomas remain a matter of speculation; however, recent understanding of NELL-1 as an integrin b1 ligand may reveal new insights.…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, in another study focusing on the effect of Nell-1 on cell migration, researchers found that Nell-1 could inhibit migration in two cancer cell lines (OS-RC-2 and VMRC-RCW). 29 Furthermore, we observed that the subcellular locations of full-length Nell-1 and Nell-1-ΔE were similar ( Figure 3A). We also analyzed the protein expression patterns of full-length Nell-1 and Nell-1-ΔE and found that full-length Nell-1 and Nell-1-ΔE exhibited similar expression patterns at the protein level in both the cell lysates and extracellular space ( Figures 3B and 3C), which was consistent with our previous report.…”
Section: Discussionmentioning
confidence: 74%
“…NELL2 was first identified as a mammalian homolog of the chicken NEL protein, and was a novel target gene of E2F1 , which was a key regulator of cell proliferation . NELL1 and NELL2 were strongly expressed in renal tubules in non‐cancerous areas of renal cell carcinoma specimens . In addition, NELL2 was trans‐activated by E2 and contributed to mediating the survival promoting effects of E2 via the intracellular signaling pathway of ERK .…”
Section: Discussionmentioning
confidence: 98%
“…22 NELL1 and NELL2 were strongly expressed in renal tubules in non-cancerous areas of renal cell carcinoma specimens. 23 In addition, NELL2 was trans-activated by E2 and contributed to mediating the survival promoting effects of E2 via the intracellular signaling pathway of ERK. 24 AGTR1 played a critical role in several diseases and was considered as a therapeutic target in ER-positive and ERBB-negative breast cancer cases.…”
Section: Discussionmentioning
confidence: 99%